PENGGUNAAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PAI SISWA KELAS V SDN 04 MUARO PAITI - Rosyahela Rosyahela; Zulfani Sesmiarni; Rodi Rodi; Edrio Mahendra (CV. ADIBA AISHA AMIRA, 2024)
Talking about educational issues, it cannot be separated from the learning process in the classroom. Learning Islamic Religious Education is a human effort to understand the universe through precise observations on targets, using correct procedures, and explaining with valid reasoning so that correct conclusions are produced. PBL (Problen Based Learning) is a learning model that accommodates student involvement in learning and authentic problem solving. The application of the PBL learning model in class V Islamic Religious Education subjects at SDN 04 Muaro Paiti based on the results of research conducted by researchers using the PBL model can improve student learning outcomes using several steps. In the PBL model the teacher plays the role of facilitator guiding learning, and students are the main center of learning. The application of the PBL learning model can improve the learning outcomes of class V Islamic Religious Education at SDN 04 Muaro Paiti, both cognitive, affective and psychomotor learning outcomes.